Identification of long non-coding RNAs expressed in knee and hip osteoarthritic cartilage. Issue 4 (April 2019) - Ajekigbe, B.; Cheung, K.; Xu, Y.; Skelton, A.J.; Panagiotopoulos, A.; Soul, J.; Hardingham, T.E.; Deehan, D.J.; Barter, M.J.; Young, D.A.
Summary: Objective: Long intergenic non-coding RNAs (lincRNAs) are emerging as key regulators in gene expression; however, little is known about the lincRNA expression changes that occur in osteoarthritis (OA). Here we aimed to define a transcriptome of lncRNAs in OA cartilage, specifically comparing the lincRNA transcriptome of knee and hip cartilage. Method: RNA-seq was performed on nucleic acid extracted from hip cartilage from patients undergoing joint replacement surgery because of either OA ( n  = 10) or because of a neck of femur fracture (NOF; n  = 6). After transcript alignment, counts were performed using Salmon and differential expression for ENSEMBL lincRNAs determined using DESeq2. Hip RNA-seq lincRNA expression was compared to a knee dataset (ArrayExpress; E-MTAB-4304). ChIP-seq data from ENCODE was used to determine whether lincRNAs were associated with promoters (plncRNA) or unidirectional enhancer-like regulatory elements (elncRNAs). Results: Our analysis of the hip transcriptome identified 1692 expressed Transcripts Per Million (TPM ≥1) Ensembl lincRNAs, of which 198 were significantly (FDR ≤0.05) differentially expressed in OA vs normal (NOF) cartilage. Similar analysis of knee cartilage transcriptome identified 648 Emsembl lincRNAs with 93 significantly (FDR ≤0.05) differentially expressed in intact vs damaged cartilage. In total, 1834 lincRNAs were expressed in both hip and knee cartilage, with a highly significant correlation in expression between the two cartilages. Conclusion: This is the first study to use RNA-seq to map and compare the lincRNA transcriptomes of hip and knee cartilage. We propose that lincRNAs expressed selectively in cartilage, or showing differential expression in OA, will play a role in cartilage homoeostasis.